Social Media Promotion of Local Brand Skincare on Generation Z’s Buying Decision - Qotrunnada, Cielomita Brilian; Marsasi, Endy Gunanto (https://jurnal.binamandiri.ac.id/, 2023)
The background of this study is because of the unoptimal concept of promotion (through) social media and the brand image among Generation Z regarding using Instagram to purchase skincare products. Brand image is used as an element of novelty to determine consumer response to purchasing decisions. The gap in this study is brand awareness of purchasing decisions, which still differs from previous studies results. This research was conducted to determine the effect of promotion (through) social media on increasing brand awareness, brand image, and purchasing decisions among consumers. The Social Learning Theory underpins this research, namely a theory that discusses the mediation process between stimuli, responses, and an individual's behavior, which is learned through observing the environment. The research object focused on local brand skincare product companies, and the subjects focused on generation Z, who use local skincare brands. Questionnaires were distributed to 220 respondents to gather the necessary data. This study conducted tests using IBM SPSS Statistics 26 software and SEM-AMOS 24. The results revealed that all hypotheses were supported. Promotion (through) social media, brand awareness, and brand image affect the purchase intention.